Aesthetic Traces in Unlikely Places: Re-visioning the Freak in 19th-Century American Photography - Sheila Moeschen (Disability Studies Quarterly, 2005)
Historically conceived as a method of truthfully depicting reality, photography serves a critical function in disseminating knowledge and constructing representations about people, places, and objects. In this essay, I examine the historical role photography has played in generating cultural conceptions of the freak in 19th-century America. By drawing a proximity between medical photographs and sideshow cartes de visites of the physically anomalous, I demonstrate a shared aesthetic tradition between science and the arts that destabilizes elements of power, authority, and control typically associated with the western medical/scientific community. My work demystifies the apparent contradiction between subjectivity and objectivity inherent in early photographic practices to reveal a strategic methodology: a way of playing with the politics of photographic representation to generate meanings for bodies that resist empirical explanation. Here, photography's structures of power and knowledge that imbricate the freak are made transparent, challenging the medium's claims to truth and "reality" that inform its critical status in contemporary American culture.
Keywords: Photography; freaks; medical science; Charcot; sideshow